Tótem [videorecording (DVD)] - Avilés, Lila; Sentíes, Naíma; Marañón, Montserrat, 1974-; Gasé, Marisol, 1972-; Gurza, Saori; García, Mateo; Sánchez, Teresa (Actress); Maldonado, Juan Francisco; Larios, Iazua; Amador, Alberto; Tenorio, Diego, 1985- (Janus contemporaries., 2024)
In a bustling Mexican household, seven-year-old Sol is swept up in the whirlwind of preparations for her terminally ill father's birthday party, led by her mother, aunts, and other relatives. As the day builds to an event both anticipated and dreaded, Sol and her family begin to understand the gravity of this year's celebration. Lila Avilés directs a dynamic ensemble cast in this stunning sophomore effort-a warmly observed, poignantly funny, and emotionally expansive study of the ways we cope with grief.